Monitoreo estacional de fitosanitarios en agua subterranea de microcuencas rurales de Pergamino - Caprile, Ana Clara; Aparicio, Virginia; De Geronimo, Eduardo; Colombini, Diego Alberto; Villalba, Fabio Leonardo; Andriulo, Adrian Enrique (Sociedad de Toxicología y Química Ambiental (SETAC), 2025)
Poster y resumen